2015
DOI: 10.1038/jp.2015.122
|View full text |Cite
|
Sign up to set email alerts
|

To evaluate and compare the efficacy of combined sucrose and non-nutritive sucking for analgesia in newborns undergoing minor painful procedure: a randomized controlled trial

Abstract: Sucrose and/or NNS are effective in providing analgesia in full-term neonates undergoing heel-stick procedures, with the combined intervention being more effective compared with any single intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 12 publications
0
37
0
2
Order By: Relevance
“…Thakar P et al evaluated analgesic effect in newborns for combined use of sucrose and non-nutritive sucking while undergoing minor painful procedure. 20 The analgesic effect of sucrose occurs firstly by activation of central endogenous opioid system an action similar to that of opioid (e.g. morphine) analgesic.…”
Section: Discussionmentioning
confidence: 99%
“…Thakar P et al evaluated analgesic effect in newborns for combined use of sucrose and non-nutritive sucking while undergoing minor painful procedure. 20 The analgesic effect of sucrose occurs firstly by activation of central endogenous opioid system an action similar to that of opioid (e.g. morphine) analgesic.…”
Section: Discussionmentioning
confidence: 99%
“…* haematological parameters, blood chemistries and hormone levels; **any other health outcome, which couldn’t be classified to any of the above listed categories (e.g. male fertility [ 289 ], offspring forearm fractures [ 290 ], emotional state [ 291 ], analgesia [ 292 ] or mortality [ 293 ]). Abbreviations: AS, artificial sweeteners; CVD, cardiovascular disease; NNS, non-nutritive sweeteners …”
Section: Resultsmentioning
confidence: 99%
“…OS and/or NNS are effective in providing analgesia in fullterm neonates undergoing heel-stick procedures, with the combined intervention being more effective compared with any single intervention. [25] Liu et al (2017) conducted a meta-analysis to evaluate the effect of combined OS and NNS for pain relief among newborns in NICU during painful procedures. They concluded that, the combination is effective not only for management but also for better prevention of procedure related pain among NICU newborns.…”
Section: Discussionmentioning
confidence: 99%